Analisis Perbandingan Kinerja Single Area dan Multi Area Menggunakan Protokol Routing OSPF - Ricky Yohanes; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
One of the dynamic routing protocols that are found on a computer network as well as being the focus of this research is Open Shortest Path First (OSPF). The application of the OSPF routing protocol can be adapted to the conditions of a network through area grouping i.e. single area and multi area. Multi area implementation can reduce the number of routes monitored, the dissemination of information becomes more orderly and segmented, reduce the calculation frequency of the routing algorithm, and reduces resource usage of the router devices that run it. Therefore, in this study used Graphical Network Simulator 3 (GNS-3) to simulate single area and multi area to find out which concept of area is the most optimal in a network condition using the OSPF routing protocol. The parameters used as the performance measurement of the routing protocols are time Convergence and roundtrip time. Roundtrip times of single area using the OSPF protocol have a value of 183.4 ms, while multi area consisting of 3 areas and 5 areas using the OSPF routing protocol have a round-trip time of 175.6 ms and 179.1 ms. The convergence time in single area using the OSPF protocol has a value of 44.6 seconds, while multi area consisting of 3 areas and 5 areas using the OSPF routing protocol have a convergence time of 43.6 seconds and 40.6 seconds.